Design of an efficient and scalable architecture for mobile ad hoc networks - Gupta Rohit. (2008)
This architecture involves a complete implementation and integration for MANET architecture by designing and implementing a zero configuration protocol, MANET routing protocol, and service discovery mechanism for different services to discover and locate each other services dynamically.